Pembelajaran Hukum Melalui Perppu Nomor 1 Tahun 2013 - Adventus Toding (The Constitutional Court of the Republic of Indonesia, 2013)
Government regulation in lieu of law is regulation released by president subjectively in force majeur condition. The change of law through the regulation is an extraordinary in nature. An extraordinary change through the government regulation in lieu of law depict a condition which put aside the change of law in normal way. The quality of the government regulation in lieu of law can be measured from the content of the regulation either from the changes made or the addition of something new that has not existed. As a regulation which contains the substance of law, the presiden’s subjectivity must objectivized through the House of Representatives. The consequence is that the regulation must be accepted or unaccepted. If accepted, then the regulation will become law. The change of law through government regulation in lieu of law will increase the qualitiy of law because enforceability of the regulation is examined empirically by the House of Representatives. Otherwise, if not acepted, the regulation will not be enforceable and evrey provision contained therein will no longer have binding force of law. Thus, the former law will prevail.